2006
DOI: 10.1111/j.1524-4725.2005.31006
|View full text |Cite
|
Sign up to set email alerts
|

High Recurrence Rates of Squamous Cell Carcinoma after Mohs' Surgery in Patients with Chronic Lymphocytic Leukemia

Abstract: The recurrence rates of squamous cell carcinoma were significantly higher in patients with chronic lymphocytic leukemia. Squamous cell carcinomas in patients with chronic lymphocytic leukemia did not exhibit a significant difference in histologic grade or clinical difference in preoperative tumor size. Close surveillance for squamous cell carcinoma recurrence is warranted in patients with chronic lymphocytic leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 30 publications
0
67
0
2
Order By: Relevance
“…The significantly greater frequency of BCC recurrence in patients with CLL after Mohs surgery correlates with 1-, 3-, and 5-year SCC recurrence rates of 4%, 15%, and 19%, respectively, in the same population. 15 In many ways, our findings raise more questions than answers. Such questions center around the contiguous tumor theory on which the efficacy of Mohs surgery is based and the role of an intact immune system in clearing tumor remnants.…”
Section: Commentmentioning
confidence: 79%
See 1 more Smart Citation
“…The significantly greater frequency of BCC recurrence in patients with CLL after Mohs surgery correlates with 1-, 3-, and 5-year SCC recurrence rates of 4%, 15%, and 19%, respectively, in the same population. 15 In many ways, our findings raise more questions than answers. Such questions center around the contiguous tumor theory on which the efficacy of Mohs surgery is based and the role of an intact immune system in clearing tumor remnants.…”
Section: Commentmentioning
confidence: 79%
“…Seven patients also had squamous cell carcinoma (SCC) and were included in a recent study of SCC recurrence rates among 28 patients with CLL. 15 All the BCCs were located on the head or neck. Twenty (83%) of the 24 patients were male.…”
Section: Resultsmentioning
confidence: 99%
“…25,26 All early-stage patients should receive age-appropriate screening for breast, prostate, and colon cancer and, where appropriate, counseling regarding smoking cessation. Due to the risk for rapid progression of non-melanomatous skin cancer, 27 we recommend a complete skin (i.e., full skin) survey on an annual basis for all patients with CLL.…”
Section: Disease-related Complicationsmentioning
confidence: 99%
“…8,9 Among those carcinomas, SCC is most common to occur. A few case reports 4,10,11 have demonstrated that, when associated with CLL/SLL, SCC of the skin behaves in a much more aggressive fashion, such as with local recurrence and extensive metastases, even resulting in death.…”
Section: Commentmentioning
confidence: 96%